The interactive dynamics of transnational business governance: A challenge for transnational legal theory. (3rd April 2015) - Wood, Stepan; Abbott, Kenneth W; Black, Julia; Eberlein, Burkard; Meidinger, Errol
Abstract : Conflict, convergence, cooperation and competition among governance actors and institutions have long fascinated scholars of transnational law, yet transnational legal theorists' accounts of such interactions are for the most part tentative, incomplete and unsystematic. Having elsewhere proposed an overarching conceptual framework for the study of transnational business governance interactions (TBGI), in this article we propose criteria for middle-range theory-building. We argue that a portfolio of theoretical perspectives on transnational governance interactions should account for the multiplicity of interacting entities and scales of interaction; the co-evolution of social agency and structure; the multiple components of regulatory governance; the role of interactions as both influence and outcome; the diverse modes of interaction; the mechanisms and pathways of interaction; and the spatio-temporal dynamics of interaction. To suggest the value of these criteria, we apply them in a preliminary way to selected transnational legal scholarship and to the other articles in this special issue.